Androgen Excess Induced Mitochondrial Abnormality in Ovarian Granulosa Cells in a Rat Model of Polycystic Ovary Syndrome - Song, Linyi; Yu, Jin; Zhang, Danying; Li, Xi; Chen, Lu; Cai, Zailong; Yu, Chaoqin (Frontiers in Endocrinology, 2022)
Background Androgen excess could profoundly lead to follicular dysplasia or atresia, and finally result in polycystic ovary syndrome (PCOS); however, the exact mechanism remains to be fully elucidated. Methods PCOS model rats were induced by dehydroepiandrosterone and their fertility was assessed. The ovarian granulosa cells (GCs) from matured follicles of PCOS model rats were collected and identified by immunofluorescence. The mitochondrial ultrastructure was observed by transmission electron microscope and the mitochondrial function was determined by detecting the adenosine triphosphate (ATP) content and mtDNA copy number. Besides, the expressions of respiratory chain complexes and ATP synthases in relation to mitochondrial function were analyzed. Results The PCOS model rats were successfully induced and their reproductive outcomes were obviously adverse. The GCs layer of the ovarian was apparently cut down and the mitochondrial ultrastructure of ovarian GCs was distinctly destroyed. The ATP content and mtDNA copy number of ovarian GCs in PCOS model rats were greatly reduced, and the expressions of NDUFB8 and ATP5j were significantly down-regulated without obvious deletion of mtDNA 4834-bp. Conclusions Androgen excess could damage mitochondrial ultrastructure and function of GCs in rat ovary by down-regulating expression of NDUFB8 and ATP5j in PCOS.